The Influence of E-Wom #Pakaisomethinc in Tiktok Towards Somethinc Consumer Perception - Putri Shinta Bella Harahap; Indria Angga Dianita (PT ARRUS Intelektual Indonesia, 2023)
Current study aims to measure the effect of electronic word of mouth (E-WOM) variables on consumer perceptions of the advertisement for the Something brand with the hashtag #PakaiSomethinc on TikTok social media. This research was conducted using quantitative methods with descriptive research types. The sampling technique used in this research is probability sampling with simple random sampling technique. Through sample calculation using the Bernoulli formula, a sample of 385 respondents was obtained. Empirical data were collected through a Google Form-based questionnaire and data were analyzed using the Normality test, heteroscedasticity test, correlation coefficient test, coefficient of determination, simple linear regression. The findings in this study indicate that the electronic word of mouth strategy which includes the quantity, credibility, and quality of information contained in the E-WOM #PakaiSomething strategy on the TikTok platform can significantly influence consumer perceptions. The results of the correlation coefficient test of 0.789 provide an understanding that the relationship between the two variables is included in the